Comparison of Efficiencies of Non-invasive Prenatal Testing, Karyotyping, and Chromosomal Micro-Array for Diagnosing Fetal Chromosomal Anomalies in the Second and Third Trimesters - Zhu, Yiyang; Shan, Qunda; Zheng, Jiayong; Cai, Qunxi; Yang, Huanli; Zhang, Jianhong; Du, Xiaodong; Jin, Fan (Frontiers in Genetics, 2019)
Aim: To compare the efficiency of karyotyping, chromosomal micro-array (CMA) and Non-invasive prenatal testing (NIPT) for diagnosing fetal chromosomal anomalies in middle and last trimesters. Design: Diagnostic test. Set: Prenatal Diagnosis Center of Taizhou City. Study Population: The pregnant women gone through amniocenteses for prenatal genetic diagnoses during the middle and late trimesters were recruited. Methods: Amniotic fluid cells were cultured for fetal karyotyping, and CMA test, and NIPT was carried out. Statistics: The diagnostic efficiency of NIPT for detecting imbalanced anomalies was compared with karyotyping and CMA. Results: Totally 69 imbalanced copy number variants (CNVs) were confirmed by CMA, 37 of them were confirmed by NIPT and 35 were found by karyotyping. The sensitivities of NIPT and karyotyping for diagnosing aneuploidy were 96.3% and 100% respectively. Only one mosaic sexual chromosome monosomy was missing diagnosed by NIPT. Whereas for detecting pathogenic deletions and duplications sized from 5-20M, the sensitivity of NIPT and karyotyping were 70% and 30%. Conclusions: The efficient of NIPT was similar to the karyotyping for detecting chromosome imbalance in 2nd and 3rd trimester. The ClinicalTrials.gov ID of this study is NCT03201666.